Democracy, development and the countryside - Varshney , Ashutosh (New Delhi, 1995)
Several scholars have written about how authoritarian or democratic political systems affect industrialization in the developing countries. There is no literature, however, on whether democracy makes a difference to the power and well-being of the countryside. Using India as a case where the longest-surviving democracy of the developing world exists, this book investigates how the countryside uses the political system to advance its interests. It is first argued that India's countryside has become quite powerful in the political system, exerting remarkable pressure on economic policy. The countryside is typically weak in the early stages of development, becoming powerful when the size of the rural sector defies this historical trend. But an important constraint on rural power stems from the inability of economic interests to overpower the abiding, ascriptive identities, and until an economic construction of politics completely overpowers identities and non-economic interests, farmers' power, though greater than ever before, will remain self-limited.
Keywords: Rural development-India